2023
DOI: 10.3390/ijms24021347
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL17A Halts the Onset of Diabetic Retinopathy in Type I and II Diabetic Mice

Abstract: There are ~463 million diabetics worldwide, and more than half have diabetic retinopathy. Yet, treatments are still lacking for non-proliferative diabetic retinopathy. We and others previously provided evidence that Interleukin-17A (IL-17A) plays a pivotal role in non-proliferative diabetic retinopathy. However, all murine studies used Type I diabetes models. Hence, it was the aim of this study to determine if IL-17A induces non-proliferative diabetic retinopathy in Type II diabetic mice, as identified for Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…(2022)[ 20 ] showed that IL-18 was considered a predictive biomarker in screening patients with kidney diseases (sensitivity 74% and specificity 82%) (Zhou et al ., 2023). [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…(2022)[ 20 ] showed that IL-18 was considered a predictive biomarker in screening patients with kidney diseases (sensitivity 74% and specificity 82%) (Zhou et al ., 2023). [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments such as panretinal photocoagulation have limitations, including potential adverse effects on visual acuity (29). Novel approaches such as CD40-TRAF6 inhibition (30) and anti-IL17A therapy (31) show promise in mouse models but require further clinical validation. These limitations underscore the pressing need for more effective and precise therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the Th17 cells in the circulation were also shown to adhere to the retinal vasculature, thus predicting to be participating in the breakdown of BRB. The IL-17A secreted into the retina binds to their receptors on Müller glial cells and photoreceptors, activating the NF-κβ pathway, Fas-associated death domain (FADD) retinal vascular endothelial cell death, as well as ERK-dependent oxidative stress resulting in retinal vascular impairment and BRB dysfunction ( 26 , 27 ). The role of photoreceptor cells in maintaining inner BRB in the diabetic retina is another emerging field.…”
Section: Blood Retinal Barrier Breakdown In Diabetic Retinopathymentioning
confidence: 99%
“…In PDR, vitreous IL-17A levels are associated with IL-10, IL-22, and TNFα levels in the aqueous humor and vitreous ( 171 ). Administering intravitreal or intraperitoneal injections of anti-IL-17A antibody or anti-IL-17RA antibody to type 1 and type 2 diabetic mice significantly reduces DR pathologies, including Müller cell dysfunction, leukostasis, leakage, downregulation of tight junction proteins, and ganglion cell apoptosis in the retina ( 27 , 172 ).…”
Section: Retinal Inflammation In Diabetic Retinopathymentioning
confidence: 99%